2016 IEEE Conference on Computer Communications Workshops (INFOCOM WKSHPS) 2016
DOI: 10.1109/infcomw.2016.7562085
|View full text |Cite
|
Sign up to set email alerts
|

Resource sharing in 5G mmWave cellular networks

Abstract: Abstract-In this paper, we discuss resource sharing, a key dimension in mmWave network design in which spectrum, access and/or network infrastructure resources can be shared by multiple operators. It is argued that this sharing paradigm will be essential to fully exploit the tremendous amounts of bandwidth and the large number of antenna degrees of freedom available in these bands, and to provide statistical multiplexing to accommodate the highly variable nature of the traffic. In this paper, we investigate an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 21 publications
2
57
0
Order By: Relevance
“…As the table reports, with the dynamic use of the spectrum, the average throughput is slightly bigger than the baseline, but more importantly, the fairness increases, which means that resources are better assigned among all the UEs. Other spectrum sharing techniques (i.e., the ones studied in [9]- [11]) can further improve the average throughput and the spectral efficiency, although drastically reducing the fairness among the UEs. Moreover, such schemes would require accurate coordination, which may be costly in dense networks.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the table reports, with the dynamic use of the spectrum, the average throughput is slightly bigger than the baseline, but more importantly, the fairness increases, which means that resources are better assigned among all the UEs. Other spectrum sharing techniques (i.e., the ones studied in [9]- [11]) can further improve the average throughput and the spectral efficiency, although drastically reducing the fairness among the UEs. Moreover, such schemes would require accurate coordination, which may be costly in dense networks.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…However, in all these survey works simulation results are missing and a detailed mmWave environment was not considered. Some simulations and numerical evaluations were presented in [9], [10] and [11]. In both [9] and [10] it is shown that spectrum sharing at mmWave has the potential for a more efficient spectrum use than a traditional exclusive spectrum allocation to a single operator.…”
Section: A Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…mmWave also enables point-to-multipoint links [86], further reducing the deployment cost. Rebato et al [87] studied how the path loss affects the mobile network deployment in terms of small-cell density and transmission power. In [88], the authors studied the path selection and the link scheduling problem for mmWave transport network as a mathematical optimization problem.…”
Section: Other Transport Technologies For Fronthaulmentioning
confidence: 99%
“…In addition to such technical gains, sharing resources translates into substantial economic profit for the mobile operators. For example, dense infrastructure is an expected need for effective mmWave coverage in 5G mobile networks and arXiv:1904.00928v1 [eess.SP] 1 Apr 2019 spectrum sharing among operators can help decrease equipment and operating costs [4]. In parallel, expenditure arising from spectrum licensing could be reduced as well.…”
Section: Introductionmentioning
confidence: 99%